Sign language translation system using kinect device - Yap, Jia Hui (Universiti Malaysia Sarawak (UNIMAS), 2018)
Sign Language Translator System play a significant role for deaf-mute people. In the old culture, manual translating sign language process induces the communication inefficiency. More time and effort were needed to translating sign language manually to other people. Therefore, this research is implemented to develop a Sign Language Translator System Using Kinect Device for effective deaf-mute people to communicate. By this era of technology, the existed sign language translating process can be optimized. In this research, a Kinect technology can integrate with sign language translation system is developed to ease the deafmute people. This system allows them to show their sign language to the system's camera and transfer the message to other people easily. System Development Life Cycle has been used as a method to develop this system. Sign Language Translator System Using Kinect Device is able to solve the problem of communication between deaf-mute people and normal communities.